The Influence Of Innovation And Competency On Employee Performance With Competitive Advantage As An Intevening Variable: Study Of Coffee Shop Employees In Limpung District - Ety Puspitaningtyas; Sutrisno Sutrisno ; Bayu Kurniawan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The Effect of Innovation and Competence on Employee Performance with Competitive Advantage as an Intervening Variable (Study of Coffee Shop Employees in Limpung District)